Where whole‐genome duplication is most beneficial: Adaptation of mangroves to a wide salinity range between land and sea - Shaohua Xu; Zixiao Guo; Xiao Feng; Shao Shao; Yuchen Yang; Jianfang Li; Cairong Zhong; Ziwen He; Suhua Shi (Molecular Ecology, 2023)
Whole‐genome duplication (WGD) is believed to increase the chance of adaptation to a new environment. This conjecture may apply particularly well to new environments that are not only different but also more variable than ancestral habitats. One such prominent environment is the interface between land and sea, which has been invaded by woody plants, collectively referred as mangroves, multiple times. Here, we use two distantly related mangrove species ( Avicennia marina and Rhizophora apiculata ) to explore the effects of WGD on the adaptive process. We found that a high proportion of duplicated genes retained after WGD have acquired derived differential expression in response to salt gradient treatment. The WGD duplicates differentially expressed in at least one copy usually (>90%) diverge from their paralogues’ expression profiles. Furthermore, both species evolved in parallel to have one paralogue expressed at a high level in both fresh water and hypersaline conditions but at a lower level at medium salinity. The pattern contrasts with the conventional view of monotone increase/decrease as salinity increases. Differentially expressed copies have thus probably acquired a new role in salinity tolerance. Our results indicate that the WGD duplicates may have evolved to function collaboratively in coping with different salinity levels, rather than specializing in the intermediate salinity optimal for mangrove plants. In conclusion, WGD and the retained duplicates appear to be an effective solution for adaptation to new and unstable environments.